Export Performance: An Analytical Focus on the Study of the Empirical Contributions of this Variable - Pineda, Berbel; Manuel, Juan; Hurtado, RamÃrez; Manuel, José (European Scientific Journal, ESJ, 2017)
There is not a unique way of measuring the performance variable as several criteria can be followed to do so. Hence, we can find objective measures (fundamentally economic-financial) and subjective measures (for example, satisfaction measures). There are many investigations which analyse this variable globally. However, this work is centred on a specific part: how an exporting activity or export performance is measured. To do so, we have carried out an analytical review of the main empirical contributions over the period 1998-2013. In this way, we have found out which is the measure, or which are the measures, of this variable that are most accepted. Furthermore, knowing the determinants of export performance will help firms' managers to direct their efforts towards those factors which foster the obtaining of good results.